External Sector Dynamics, Investment and Economic Growth in Nepal: A VECM Perspective - Poudel, Anish (Interdisciplinary Journal of Management and Social Sciences, 2025)
This study investigates the dynamic relationships between Nepal’s real GDP, exports, imports, and gross fixed capital formation (GFCF) using a Vector Error Correction Model (VECM), with remittances included as a control variable. Using annual data from 1975 to 2023, the analysis shows the presence of two long-run cointegration relationships among these variables. The results reveal that while exports negatively impact GDP, they contribute positively in the long run. Imports, particularly of capital and intermediate goods, enhance economic growth in the short term but may lead to external imbalances without corresponding export growth. GFCF remains the primary driver of GDP expansion in both the short and long run. The error correction mechanism suggests that deviations from the long-run equilibrium are corrected at a speed of 56.7% per period. Variance decomposition analysis highlights the growing role of investment in sustaining exports, while GDP growth largely influences imports. The findings emphasize the need for policies that enhance export competitiveness, optimize imports for productive use, and promote investment-driven economic growth to ensure Nepal’s long-term macroeconomic stability.